(untitled) (World Bulletin of Management and Law, 2022)
The current study tests the correlation and influence relationship between the integration of knowledge (direction, exchange, socialization, comprehension) and the behavior of sharing knowledge with its dimensions (fairness, identity, enjoyment of help, openness, interest/knowledge, the behavior of sharing knowledge). Between the integration of knowledge and the behavior of knowledge-sharing, from which six sub-hypotheses emerge, and then a sample of 127 teaching staff was selected at the Technical Institute / Al-Musayyab, which is of vital and prominent importance in the field of education and knowledge and its diverse practices in creating an educated, civilized and educated generation. The data were collected through a questionnaire prepared For this purpose, 127 questionnaires were distributed to the teaching staff, 110 were retrieved, and the recovery rate was 87%. SPSS vr programs were used. 24 To extract the results of correlation and influence and test hypotheses, as the validity of the hypotheses was found in the light of the results of the statistical analysis, and a number of recommendations were reached, perhaps the most prominent of which is the existence of a vital and prominent effect of knowledge integration in the behavior of knowledge sharing.